1999
DOI: 10.1046/j.1440-1819.1999.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three principal constituents in chewing gum on electroencephalographic activity

Abstract: The effects of three principal constituents (sugar, spearmint, and gumbase) in chewing gum on EEG findings in 20 normal subjects were investigated. After they chewed the gumbase, theta activity decreased significantly at Fp2, O1, T3, T4, F4, P3, and Pz; alpha activity increased significantly at O1 and decreased significantly at Fp1, and beta activity increased significantly at Fp1, Fp2, O1, T3, T4, P3 and Pz. After they inhaled the spearmint, alpha activity decreased significantly at 02, F3, P4, and Fz, and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
2
23
2
Order By: Relevance
“…Further research is now required to determine the practical implications of the alerting effect of chewing gum and to understand the brain mechanisms that underlie such changes. However, the alerting effects of chewing gum are consistent with results from EEG studies 13,14 and it has been suggested that chewing gum activates at least two types of mechanism, one related to the chewing and the other to the flavour of the gum. 14,15,25 Studies measuring EMG confirm that EMG activity in particular facial muscles is related to the mobilization of energetic resources.…”
Section: Discussionsupporting
confidence: 82%
“…Further research is now required to determine the practical implications of the alerting effect of chewing gum and to understand the brain mechanisms that underlie such changes. However, the alerting effects of chewing gum are consistent with results from EEG studies 13,14 and it has been suggested that chewing gum activates at least two types of mechanism, one related to the chewing and the other to the flavour of the gum. 14,15,25 Studies measuring EMG confirm that EMG activity in particular facial muscles is related to the mobilization of energetic resources.…”
Section: Discussionsupporting
confidence: 82%
“…Inhalation of essential oils of eucalyptus, lavender and spiced oil have been found to possess potent and positive effects on EEG activity [10]. In contrary to our results, Masumoto et al [18] reported that the inhalation of aroma of spearmint oil significantly decreased alpha and increased theta activities. Then the authors suggested that the spearmint oil induced arousal effects.…”
Section: Resultscontrasting
confidence: 99%
“…6,9 EEG studies also suggest that chewing gum may increase alertness 25,26 and it has been suggested that chewing gum activates at least two types of mechanism, one related to the chewing and the other to the flavour of the gum. 7,26 In addition, studies measuring EMG confirm that EMG activity, in particular facial muscles, is related to the mobilization of energetic resources. 27 Mastication also has effects on both sympathetic and parasympathetic activity.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it was important to determine whether effects of gum generalize across gum types (in this case mint and fruit flavors) as some studies suggest that it is the flavor of the gum that is important. 7 There is considerable anecdotal evidence that individuals who are stressed or anxious often chew gum. Smith 8 has recently investigated the personality characteristics associated with chewing gum and found that high consumers of gum are more anxious.…”
Section: Introductionmentioning
confidence: 99%